2007
DOI: 10.2478/s11756-007-0134-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seed extracts of Withania somnifera, Croton tiglium and Hygrophila auriculata on behavior and physiology of Odontotermes obesus (Isoptera, Termitidae)

Abstract: In addition to antibiotic properties, medicinal plants are important sources of chemicals with potential application as pesticides. The present study deals with antitermitic potential of seed extracts of Withania somnifera (Indian ginseng), Croton tiglium (jamalgoota) and Hygrophila auriculata (talimkhana). The seed extracts caused changes in tunneling behaviour, number of bacterial colonies in hindgut and activities of enzymes in midgut of Odontotermes obesus. C. tiglium showed the lowest LT50 (12.85 and 2.65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…This confirms effectiveness of the oil extract solution in enhancing decay resistance of wood [40]. The results of this study corroborate the findings of [41] and [42] who reported that seeds extract of medicinal plants such as Parquetina nigrescens could be used as fungi controlling agents. High alkaloids and tannins content in the P. nigrescens leaf extract could be responsible for antifungal property observed in the treatments with lower weight loss.…”
Section: B Absorption Of Bio-preservative Formulationssupporting
confidence: 91%
“…This confirms effectiveness of the oil extract solution in enhancing decay resistance of wood [40]. The results of this study corroborate the findings of [41] and [42] who reported that seeds extract of medicinal plants such as Parquetina nigrescens could be used as fungi controlling agents. High alkaloids and tannins content in the P. nigrescens leaf extract could be responsible for antifungal property observed in the treatments with lower weight loss.…”
Section: B Absorption Of Bio-preservative Formulationssupporting
confidence: 91%
“…Secondary metabolites of sponges were found to have potential larvicidal and pesticidal effects against P. ricini (Joseph et al 2010). Botanical insecticide, azadirachtin disrupted physiological processes such as apolysis and ecdysis and induced morphological deformities at larval and pupal stages of P. ricini (Gnanamani and Dhanasekaran 2013). Ethyl acetate extracts of Tragia involucrata showed antifeedant, larvicidal and growth inhibitory effects against this agriculturally important pest, P. ricini .…”
Section: Introductionmentioning
confidence: 99%
“…Several other research works (Singh and Sushilkumar 2008;Sotannde et al 2011;Djenontin et al 2012;Addisu et al 2014;Faruwa et al 2015) have also reported the efficacy of plants extractsas bio-preservative against fungi and termite attacks. Mazhar et al, (2013) affirmed that the seed extracts of medicinal plant offers a source of naturally occurring chemicals that could be used because of the repellent, anti-feedant or toxic effects on micro-organisms in feeding assays (Ahmed et al 2007. (Okanlawon et al, 2020) which could also be attributed to variations in physical and anatomical characteristics of Triplochiton scleroxylon wood specie and also probably due to the wood of C. petandra being lighter, softer in texture and lower in strength and coarser (Gibbs and Semir, 2003).…”
Section: Resultsmentioning
confidence: 99%